1998
DOI: 10.1021/ie980077k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Active Hydrodesulfurization Carbon-Supported Co−Mo Catalysts. Relationships between Preparation Methods and Activity/Selectivity

Abstract: Several series of Co−Mo-based carbon catalysts series were synthesized using three methods, successive impregnation, successive impregnation with sulfidation in between, and equilibrium adsorption methods. Co/C and Mo/C were also prepared by impregnation. The activities of sulfided catalysts for hydrodesulfurization of dibenzothiophene (DBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT) as models of the most refractory sulfur-containing compounds found in petroleum oil were studied using an autoclave reactor op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 35 publications
(50 reference statements)
1
26
0
Order By: Relevance
“…The only products detected in all runs were phenyl- cyclohexane, biphenyl, and the partially hydrogenated dibenzothiophene (H4-DBT), in agreement with results found in the literature (1,3,4). The activity of the catalysts for hydrodesulfurization of dibenzothiophene is represented in Table 3.…”
Section: Hydrodesulfurization Activity Of Como Catalystssupporting
confidence: 89%
See 1 more Smart Citation
“…The only products detected in all runs were phenyl- cyclohexane, biphenyl, and the partially hydrogenated dibenzothiophene (H4-DBT), in agreement with results found in the literature (1,3,4). The activity of the catalysts for hydrodesulfurization of dibenzothiophene is represented in Table 3.…”
Section: Hydrodesulfurization Activity Of Como Catalystssupporting
confidence: 89%
“…Most of these catalysts consist of transition metals or transition metal oxides loaded on an appropriate support and synthesized via the conventional impregnation. The basic role of which is to maintain the catalytically active phase in a highly dispersed state (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…benzothiophenes with no substituents in 2-or 7-position 2. dibenzothiophenes with no substituents in the 4-or 6-position 3. dibenzothiophenes with one substituent in the 4-position 4. dibenzothiophenes with two substituents in the 4-and 6-positions For these distillates to meet the mandated sulfur specifications, all compounds in groups 1, 2, and 3 will have to be completely desulfurized, and at least half of those in the least-reactive fourth group will also have to be converted. Several studies using different types of catalysts and operating conditions have identified 4-methyldibenzothiophene (4-MDBT) and 4,6-dimethyldibenzothiophene (4,6-DMDBT) as the most refractory sulfur compounds which will have to be eliminated to achieve deep desulfurization [49,50,[63][64][65][66][67][68][69][70].…”
Section: Reactivity Of Poly Aromatic Sulfur Compoundsmentioning
confidence: 99%
“…In particular, sulfides of Group VIB (molybdenum and tungsten) and Group VIII (cobalt, nickel) are of great industrial interest due to they are widely used in petroleum refining for hydroprocessing applications. Moreover, these sulfides are active in catalytic coal liquefaction [1], i.e., in breaking up macromolecules into low molecular weight fragments.…”
Section: Introductionmentioning
confidence: 99%